If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x-2)(x=6)=180
We move all terms to the left:
(x-2)(x-(6))=0
We multiply parentheses ..
(+x^2-6x-2x+12)=0
We get rid of parentheses
x^2-6x-2x+12=0
We add all the numbers together, and all the variables
x^2-8x+12=0
a = 1; b = -8; c = +12;
Δ = b2-4ac
Δ = -82-4·1·12
Δ = 16
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{16}=4$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-8)-4}{2*1}=\frac{4}{2} =2 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-8)+4}{2*1}=\frac{12}{2} =6 $
| 4(p-7)=3p-32 | | 16+19x+15=71-x | | 180=6x-9+7x+7 | | 118-x=4+5x | | 8(p-6)=7p-51 | | Y=-18x+15 | | Y=21x+11 | | 7+16=142+x | | 180=25x+20x | | -5p-2.9=-6p-3.2 | | 4b-4+18+28+3b=70 | | I2x-5I=99 | | 8p+83/9=3 | | 180=2x+13+x+40 | | 16x+40=11x-4 | | 180=6x+2+11x+8 | | (9x+4)/3=5 | | (3x+1)=2(x+6) | | r/18=23 | | w+196=981 | | v/19=29 | | 895=v+71 | | z+133=388 | | b/18=26 | | p-149=5 | | j-122=218 | | 589=31c | | 93=h+1 | | m-73=18 | | g-51=37 | | v-93=2 | | 87=h+37 |